The Strategic Role of Parents in Optimizing Character Education in Early Childhood in the Family Environment - I Gede Sujana; Anak Agung Gde Putera Semadi; Ni Made Suarningsih; Elly Retnaningrum; Reviandari Widyatiningtyas; I Gusti Ngurah Santika (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
So far, the role of parents in educating the character of their young children in the family environment has not run optimally. Whereas parents have an important role in shaping children's character. The purpose of this research was to determine the strategic role of parents in optimizing character education in early childhood in the family environment. The method used in this research was descriptive qualitative. The sampling technique used in this research is snowball sampling. Data collection techniques used were observation, interviews and documentation (triangulation). The data analysis used was the Miles and Huberman model. The results of this research indicated that the role of parents in optimizing character education in early childhood is carried out by example, providing free time, advice, motivation, habituation and punishment. But not all families implement this role in optimizing their children's character education. From the 10 families studied, it was found that 10 families applied the role of parents by exemplary, 6 families provided leisure time, 8 families received advice, 7 families by motivation, 10 families had habituation and 10 families by punishment. This research needs to be expanded and deepened again by adding samplest